Study of the complexity of Spanish for textual simplification - Araya Camposa, Randall (2020)
Most of the work in the area of ​​textual simplification is done on the languageEnglish for having more linguistic resources and about the journalistic genre. But nevertheless,Due to our context, in this work we concentrate on studying and automating the metricsexisting to measure lexical complexity for Spanish, as a previous step to identifyingof complex sentences and their subsequent simplification. Another novel aspect of this workis the use of corpus related to human rights, specifically of theOrganization for the United Nations and the United Nations High Commissioner forRefugees. The most significant contributions are: the creation of a code toolopen, which generates a report on the complexity of a given text in order to supportto anyone interested in simplifying that text, and the proposal of a new metric to measurecomplexity in a multifaceted way. The results obtained in the different experimentscarried out are promising and in many cases confirm the hypotheses raised.